Pediatric Emergency Medicine Simulation Curriculum: Blunt Abdominal Trauma - Jennifer Reid; Kimberly Stone; Jeffrey Otjen (Association of American Medical Colleges, 2015)
Abstract Injury in general, is the leading cause of death for children in the United States and most developed countries. Blunt abdominal trauma occurs in 10-15% of injured children, with two typical patterns: isolated injury caused by a direct blow or as a part of a high-mechanism, multisystem trauma. Rapid identification of blunt abdominal trauma and its potential sequelae (e.g., hemorrhagic shock, bowel injury) is critical. Management should include monitoring, supplemental 100% oxygen, recruitment of additional resources, airway protection, and intravascular volume replacement. Rapid sequence intubation should be considered for unstable patients. Definitive care may only be available at trauma centers; thus, prompt transfer to a pediatric trauma facility may be critical. The goal of this scenario is to provide the learner with an opportunity to manage pediatric blunt abdominal trauma with hemorrhagic shock, where the correct steps need to be taken in a limited period of time. We included extensive preparatory material, to help the instructor prepare the environment and learners. The debriefing tools have been tailored specifically for this scenario, with advice on how the instructor can edit them for different learners. Supplemental learner handouts help reinforce teaching points. In addition, handouts reviewed by learners who are not able to attend a specific session generate questions amongst the residents themselves and more interest for future simulation sessions. The inclusion of a learner feedback form promotes continuous improvement of the scenario, environmental preparation, and debriefing. In addition, it helps faculty document their teaching efforts. As part of the larger pediatric emergency medicine curriculum which features recurring educational goals and objectives, we found that learners' performance (in medical management, technical skills, and teamwork) improves over time.